Weighting across safeguard subjects for LCIA through the application of conjoint analysis - Itsubo, Norihiro; Sakagami, Masaji; Washida, Toyoaki; Kokubu, Katsuhiko; Inaba, Atsushi (The international journal of life cycle assessment, 2004)
BackgroundMany types of weighting methods, which have integrated the various environmental impacts that are used for life-cycle impact assessment (LCIA), were proposed with the aim of developing the methodology as a useful information resource for decision making, such as in the selection of products. Economic valuation indexes, in particular, have attracted attention, as their assessment results are easy to understand and can be applied in conjunction with other assessment tools, including life-cycle costing (LCC) and environmental accounting. Conjoint analysis has been widely used in market research, and has recently been applied to research in environmental economics. The method enables us to provide two types of assessment results; an economic valuation and a dimensionless index. This method is therefore expected to contribute greatly to increasing the level of research into weighting methodology, in which an international consensus has yet to be established. Conjoint analysis, however, has not previously been applied to LCIA.ObjectiveLCA National Project (METI/NEDO/JEMAI) has conducted a study aimed at the development of a Japanese version of the damage-oriented impact assessment method called LIME (Life-cycle Impact assessment Method based on Endpoint modeling), in order to enhance its reliability and transparency. This study aimed at the application of conjoint analysis to the step of weighting in LIME. An ultimate goal of the research is to determine an amount of willingness to pay (WTP) for avoiding a unit quantity of damage of every safeguard subject (endpoint).MethodsPotential annual damages of four safeguard subjects (human health, biodiversity, social assets, and primary production), known as normalization values in LCIA, were used as fundamental information in this study. These data can be obtained through damage assessment. Taking this background into account, we performed a comparison of importance among the four safeguard subjects defined in LIME by applying conjoint analysis. A choice-based type of questionnaire was prepared for the interview with the respondents selected by random sampling. Pre-tests were conducted for 108 respondents in advance of the main survey. After we confirmed that the analyzed results of the pre-test were revealed to be statistically significant, the main surveys were conducted for 400 respondents by interviewing. WTP per quota can be determined by statistical simulation based on the random utility theory reflecting the responses to the questionnaires by random sampling.Results and DiscussionThe values of one unit (standard) of attributes were significant statistically at the 1% level (all of the p value for coefficients of safeguard subjects were less than 0.0001). Based on the calculated results, two types of weighting factors, an economic valuation and a dimensionless index were obtained. The capability of generating two kinds of weighting factors is unique to conjoint analysis. A relative comparison of importance among the four categories indicates that human health gains the highest recognition, biodiversity gains the second highest recognition, and the weight of primary production and social assets have been estimated to be relatively smaller than the other two safeguard subjects.ConclusionIt is desirable to prepare a small number of attributes when conducting a conjoint analysis, because the efforts of respondents have to be reduced as far as possible. We confirmed that the damage-oriented method, which minimizes the number of attributes, is suitable to the requirement of conjoint analysis, because the results of comparisons among safeguard subjects were statistically significant, and showed that the contents of the questionnaires were well understood among the respondents. Judging from the results of this study, where statistical significance has not even been fully verified in the conventional research on the development of weighting coefficients for LCIA, it can be concluded that the weighting factors derived from this study based on the economic theory have a possibility to reveal the impact of environment on society.